(untitled) (Acta Scientiarum. Animal Sciences, 2019)
The purpose of this study was to investigate the effects of four types of diets containing different forms of selenium on the hematological blood parameters, reproduction and health of dairy cattle during the transition period. Twenty-four close-up dry cows with a mean of 259 ± 1days of pregnancy and expected 21 ± 1days prior to parturition were selected. The cows were fed four diets: 1) basal diet without selenium supplementation (C); 2) basal diet plus 0.5ppm selenium in the form of sodium selenite (Se-S) 3) basal diet plus 0.5ppm selenium in the form of selenium yeast (Se-Y); 4) basal diet plus 0.5ppm selenium in the form of selenomethionine (Se-M). Blood samples for measuring hematological blood parameters (including lymphocyte, red blood cells, hemoglobin, and hematocrit, MCV, MCH, MCHC and RDWc) were taken at 21 and 10 days before delivery, delivery date, 10 and 21 days after delivery. There was no significant difference in hematological parameters before and after delivery in experimental and control groups. However, in the prepartum period, MCH tended to increase significantly in selenium methionine treatment (p<0.05). Reproductive parameters (including distance to first estrus, insemination indexes and number of open days) and health parameters (including rectum temperature and vaginal content score) have been improved by selenium organic supplements. The results of this experiment showed that feeding organic selenium supplementation in multiparous dairy cow’s diet may improve their health and reproduction.